2013
DOI: 10.1074/jbc.m113.477976
|View full text |Cite
|
Sign up to set email alerts
|

Association/Dissociation of the Nucleotide-binding Domains of the ATP-binding Cassette Protein MsbA Measured during Continuous Hydrolysis

Abstract: Background:In ATP-binding cassette proteins, ATP binding produces association of the two nucleotide-binding domains (NBDs), but the molecular mechanism is unknown. Results: The NBDs separate following ATP hydrolysis. Conclusion: NBD dimers dissociate during the hydrolysis cycle supporting monomer/dimer models of operation. Significance: Knowledge of the molecular mechanism of hydrolysis will help us understand how ATP-binding cassette proteins work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
67
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(81 citation statements)
references
References 41 publications
13
67
1
Order By: Relevance
“…Several studies point to large motions between the nucleotide-free "open" inward-facing conformation (NBDs separated by tens of Angstroms) and the ATP-bound "closed" outward-facing conformation (tightly associated NBDs). These observations disagree with evidence suggesting that the NBDs remain in close contact at all times during the transport cycle and that such large conformational changes might not be physiological (19 -22).For simplicity and because of technical limitations, essentially all structural studies of ABC exporters have been performed with the proteins solubilized in detergent, locked in specific conformations and/or at low temperature (11,12,14,18,(23)(24)(25)(26). However, understanding of the structure-function of membrane proteins requires their study under more physiological conditions, at a minimum: 1) reconstitution into lipid bilayers, their native environment; 2) physiological temperatures; and 3) functioning conditions, as opposed to specific locked conformations.…”
contrasting
confidence: 44%
See 4 more Smart Citations
“…Several studies point to large motions between the nucleotide-free "open" inward-facing conformation (NBDs separated by tens of Angstroms) and the ATP-bound "closed" outward-facing conformation (tightly associated NBDs). These observations disagree with evidence suggesting that the NBDs remain in close contact at all times during the transport cycle and that such large conformational changes might not be physiological (19 -22).For simplicity and because of technical limitations, essentially all structural studies of ABC exporters have been performed with the proteins solubilized in detergent, locked in specific conformations and/or at low temperature (11,12,14,18,(23)(24)(25)(26). However, understanding of the structure-function of membrane proteins requires their study under more physiological conditions, at a minimum: 1) reconstitution into lipid bilayers, their native environment; 2) physiological temperatures; and 3) functioning conditions, as opposed to specific locked conformations.…”
contrasting
confidence: 44%
“…We found that MsbA reconstituted in nanodiscs, and at physiological temperature, showed major differences with the published crystal structure in the open inward-facing conformation, as well as with double electron-electron resonance (DEER) experiments and LRET experiments performed with MsbA in detergent micelles (11,13,14,18).…”
Section: Atp-binding Cassette (Abc)mentioning
confidence: 87%
See 3 more Smart Citations